2013
DOI: 10.1088/0004-637x/763/1/46
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Non-Steady Spiral Arms in Disk Galaxies

Abstract: In order to understand the physical mechanisms underlying non-steady stellar spiral arms in disk galaxies, we analyzed the growing and damping phases of their spiral arms using three-dimensional N -body simulations. We confirmed that the spiral arms are formed due to a swing amplification mechanism that reinforces density enhancement as a seeded wake. In the damping phase, the Coriolis force exerted on a portion of the arm surpasses the gravitational force that acts to shrink the portion. Consequently, the sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
210
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(235 citation statements)
references
References 65 publications
(100 reference statements)
18
210
2
Order By: Relevance
“…In recent years, it was found that the nonlinear effect is significant to understand the overall activity of the spiral arms (e.g., Baba et al 2013;D'Onghia et al 2013). We found that the linear theory can predict the correct pitch angle that is consistent with the numerical simulation.…”
Section: Resultssupporting
confidence: 79%
“…In recent years, it was found that the nonlinear effect is significant to understand the overall activity of the spiral arms (e.g., Baba et al 2013;D'Onghia et al 2013). We found that the linear theory can predict the correct pitch angle that is consistent with the numerical simulation.…”
Section: Resultssupporting
confidence: 79%
“…4.5. The origin of spiral arms in cosmological zoom-in simulations Modern theoretical efforts in understanding the origin of spiral arms have focused on semi-analytic or N-body simulations in isolated disks (e.g., Wada et al 2011;Baba et al 2013;D'Onghia et al 2013;D'Onghia 2015). Cosmological simulations do not have sufficient resolutions to trace the detail dynamics of spiral arms, however, it is interesting to explore the spiral arm formation from the context of cosmological simulations where the role of environment is included.…”
Section: Spiral Arm and Thin Disk Formationmentioning
confidence: 99%
“…9 is slight). The leading cause of this difference may be related to either the different stages of spiral arm formation and disruption (see, for example, Baba et al 2013), or the different pitch angle of the spiral arm at these instances. A further detailed study is required to determine the cause.…”
Section: Evolutionary Stage Of the Spiral Armmentioning
confidence: 99%